Use of traditional medicine for self-medication in the community of Bulutellue village, Sinjai Regency - Abdul Rahman (Rayhan Intermedia, 2026)
This study aims to explore the practice of self-medication using traditional medicine among the community of Bulutellue Village, Sinjai, through a medical anthropology perspective. Employing a qualitative approach with ethnographic methods, data were gathered through participant observation and in-depth interviews with local residents and traditional figures. The findings reveal that the use of herbal concoctions is not merely an effort for physical healing, but a form of preserving indigenous knowledge passed down through generations. The community perceives health as a balance between humans and nature, where the selection of medicinal plants is deeply influenced by cultural beliefs and local biodiversity. This self-medication behavior reflects a folk medicine system that persists amidst the currents of medical modernization. The study concludes that socio-cultural factors and ancestral symbolic capital are the primary drivers for the community’s preference for traditional remedies over modern pharmacy for minor health complaints, reinforcing their collective cultural identity.